Factors influencing colorectal cancer screening decisions among Saudi women: A qualitative study - Norah Alsadhan; Cathy Brennan; Sultana A. Alhurishi; Farag Shuweihdi; Robert M. West (PLoS ONE, 2025)
Background Colorectal cancer (CRC) is a major global health challenge and one of the most prevalent cancers in Saudi Arabia. Studies show that young Saudi women are often diagnosed with CRC at more advanced stages, leading to poorer prognoses. Despite the recent launch of the first Saudi national CRC screening program, public awareness and acceptance of CRC screening (CRCS) remain limited. Methods We conducted semi-structured interviews with 17 women aged 40 or older to explore their awareness, views, and attitudes toward CRC and CRCS. Data were analyzed using reflexive thematic analysis, and the Social Ecological Model was applied to guide the structuring and organization of the developed themes. Results We identified a multifaceted interplay of knowledge, beliefs, and social-cultural factors influencing CRCS decisions among Saudi women. Although there was a general awareness of CRC, understanding of risk factors, signs, and symptoms was limited. Many participants adopted a reactive approach to screening, prompted by symptom manifestation or family history, rather than preventive health measures. Concerns such as fear of a cancer diagnosis and discomfort with the stool sample collection process hindered screening participation. Social support from family and community, and physician recommendations were crucial in encouraging screening uptake. Logistic and digital literacy challenges in accessing health services were noted for older adults. Participants stressed the need for increased CRC awareness, equitable access to screening services, and reminders to improve CRCS participation. Conclusion Factors influencing CRCS uptake among Saudi women are complex and multifaceted. Comprehensive and tailored health promotion interventions that meet community needs are essential. Further research is needed to develop and evaluate the effectiveness of these interventions in increasing screening uptake.